Developmental Themes in the Narrative of Adults with Early International Experiences - Abe, Jo Ann A. (Journal of Adult Development, 2023)
This study extends research on adult narrative identity in two major ways. First, it focuses on Adult Third Culture Kids (ATCKs), which refer to individuals who spent a part of their early developmental years abroad. In spite of the fact that they are an important demographic to study in this rapidly globalizing world, they have tended to be neglected in the field of psychology. Second, this study incorporates the cutting-edge tools of automated language analysis to extract developmental themes from autobiographical narratives using a bottom-up exploratory approach, as well as to identify psychological patterns and processes associated with the themes. The participants (N = 350; 18–80 + years old) were recruited from an alumni office of an international school and asked to write a narrative about the impact their international experiences had on their development. The meaning extraction method (MEM) yielded four developmental themes, which were remarkably consistent with the recurring themes that emerge from past research on adult narrative identity as well as ATCKs: past focus, communion, agency, and global focus. These four developmental themes, in turn, showed theoretically coherent patterns of relations with the demographic variables, linguistic markers of psychological patterns and processes, as well as self-reports of dimensions of well-being.
Keywords: Adult third culture kids (ATCKs); LIWC; MEH; Meaning extraction method; Narrative identity; dept.psy; peer-reviewed

Event-Related Potentials in Assessing Visual Speech Cues in the Broader Autism Phenotype: Evidence from a Phonemic Restoration Paradigm - Harwood, Vanessa; Baron, Alisa; Kleinman, Daniel; Campanelli, Luca; Irwin, Julia; Landi, Nicole (Brain Sciences, 2023)
Audiovisual speech perception includes the simultaneous processing of auditory and visual speech. Deficits in audiovisual speech perception are reported in autistic individuals; however, less is known regarding audiovisual speech perception within the broader autism phenotype (BAP), which includes individuals with elevated, yet subclinical, levels of autistic traits. We investigate the neural indices of audiovisual speech perception in adults exhibiting a range of autism-like traits using event-related potentials (ERPs) in a phonemic restoration paradigm. In this paradigm, we consider conditions where speech articulators (mouth and jaw) are present (AV condition) and obscured by a pixelated mask (PX condition). These two face conditions were included in both passive (simply viewing a speaking face) and active (participants were required to press a button for a specific consonant–vowel stimulus) experiments. The results revealed an N100 ERP component which was present for all listening contexts and conditions; however, it was attenuated in the active AV condition where participants were able to view the speaker’s face, including the mouth and jaw. The P300 ERP component was present within the active experiment only, and significantly greater within the AV condition compared to the PX condition. This suggests increased neural effort for detecting deviant stimuli when visible articulation was present and visual influence on perception. Finally, the P300 response was negatively correlated with autism-like traits, suggesting that higher autistic traits were associated with generally smaller P300 responses in the active AV and PX conditions. The conclusions support the finding that atypical audiovisual processing may be characteristic of the BAP in adults.
1 citations (Crossref) [2023-10-31] Number: 7
Keywords: audiovisual; dept.psy; event-related potentials; peer-reviewed; phonemic restoration; speech perception